A subnanomolar concentration of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) pre-synaptically modulates glutamatergic transmission in the rat hippocampus acting through acetylcholine. (6th January 2017) - Pecoraro, Valeria; Sardone, Lara Maria; Chisari, Mariangela; Licata, Flora; Li Volsi, Guido; Perciavalle, Vincenzo; Ciranna, Lucia; Costa, Lara
Highlights: High-affinity PAC1 receptors induce ACh-mediated effects in the hippocampus. PAC1 receptors pre-synaptically modulate glutamatergic synaptic transmission through ACh. PACAP at very low doses might be beneficial in cognitive diseases with reduced cholinergic transmission. Abstract: The neuropeptide PACAP modulates synaptic transmission in the hippocampus exerting multiple effects through different receptor subtypes: the underlying mechanisms have not yet been completely elucidated. The neurotransmitter acetylcholine (ACh) also exerts a well-documented modulation of hippocampal synaptic transmission and plasticity. Since PACAP was shown to stimulate ACh release in the hippocampus, we tested whether PACAP acting through ACh might indirectly modulate glutamate-mediated synaptic transmission at a pre- and/or at a post-synaptic level. Using patch clamp on rat hippocampal slices, we tested PACAP effects on stimulation-evoked AMPA receptor-mediated excitatory post-synaptic currents (EPSCsAMPA ) in the CA3-CA1 synapse and on spontaneous miniature EPSCs (mEPSCs) in CA1 pyramidal neurons. A subnanomolar dose of PACAP (0.5 nM) decreased EPSCsAMPA amplitude, enhanced EPSC paired-pulse facilitation (PPF) and reduced mEPSC frequency, indicating a pre-synaptic decrease of glutamate release probability: these effects were abolished by simultaneous blockade of muscarinic and nicotinic ACh receptors, indicating the involvement of endogenous ACh. The effect of subnanomolar PACAP was abolished by a PAC1 receptor antagonist but not by a VPAC receptor blocker. At a higher concentration (10 nM), PACAP inhibited EPSCsAMPA : this effect persisted in the presence of ACh receptor antagonists and did not involve any change in PPF or in mEPSC frequency, thus was not mediated by ACh and was exerted post- synaptically on CA1 pyramidal neurons. We suggest that a high-affinity PAC1 receptor pre-synaptically modulates hippocampal glutamatergic transmission acting through ACh. Therefore, administration of PACAP at very low doses might be envisaged in cognitive diseases with reduced cholinergic transmission.